2019
DOI: 10.1038/s41379-019-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of low- and high-grade appendiceal mucinous neoplasms by targeted sequencing of cancer-related variants

Abstract: DNA was obtained from matching micro-dissected, primary tumor cells, paired metastases, and peripheral blood mononuclear cells (germline) from patients with appendiceal mucinous neoplasms. We compared specimens from patient cohorts comprising low-grade adenomucinous neoplasm versus high-grade mucinous adenocarcinoma using a targeted, amplicon sequencing panel of 409 cancer related genes (Ion Torrent Comprehensive Cancer Panel, Thermo-Fisher, Waltham, MA). Copy number variants, single nucleotide variants and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…The 8q and 21q gains were unique to the PMPs. We observed CNV gains in chromosome 1q and 20q that have been previously identified in mucinous neoplasms of the appendix [25,26].…”
Section: Genomic Instability In Neoplastic Goblet Cells From Amns And...supporting
confidence: 70%
“…The 8q and 21q gains were unique to the PMPs. We observed CNV gains in chromosome 1q and 20q that have been previously identified in mucinous neoplasms of the appendix [25,26].…”
Section: Genomic Instability In Neoplastic Goblet Cells From Amns And...supporting
confidence: 70%
“…The high incidence of KRAS mutations in appendiceal cancers distinguishes them from colorectal cancers and may partially explain their limited response to systemic chemotherapies 40 . Likewise, GNAS mutations are reported in 50%‐72% of AMN, but without correlation to clinical outcomes 41‐43 . Both patients had GNAS mutations at the same loci, but different base substitutions (mother: R201H; daughter: R201C).…”
Section: Discussionmentioning
confidence: 99%
“…40 Likewise, GNAS mutations are reported in 50%-72% of AMN, but without correlation to clinical outcomes. [41][42][43] Both patients had GNAS mutations at the same loci, but different base substitutions (mother: R201H; daughter: R201C). Borazanci et al profiled 588 appendiceal tumors and found that AMN have approximately the same incidence of GNAS mutations as intraductal papillary mucinous neoplasms, suggesting that it may play a role in disease development and mucin production, and have similar molecular profiles to pancreatic cancers.…”
Section: Daughter Onlymentioning
confidence: 99%
“…This relatively low rate of GNAS mutation in LAMNs might be due to the low sensitivity of Sanger sequencing and limited exon coverage. Alakus and other researchers [24][25][26][27] also proposed that coexisting mutations of KRAS and GNAS were characteristic to LAMN and KRAS mutation occurs earlier in the course of tumorigenesis. This pathway was also shared by IPMN.…”
Section: Discussionmentioning
confidence: 99%